Konsep Masa Berlaku Perlindungan Hak Cipta Perspektif Hukum Islam - Achmad Baihaqi; Said Abadi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The issue of Intellectual Property Rights has not been discussed or even described by classical fiqh scholars in-depth and thoroughly. One aspect that has not been studied is the issue of the period of copyright protection. The assumption is that if copyright protection is not limited in time, it will lead to a monopoly of creation by a few people. Therefore, the purpose of this study is to clearly describe and compare the terms of copyright protection in the Copyright Act and Islamic Law using the Maqashid Syariah perspective. The method used is a qualitative study (library research) with a comparative approach. The results of the study indicate that the period of copyright protection according to Islamic law, for the type of moral rights is valid forever, while for the type of economic rights it applies trade (willingness of the heart) with the provision that the shorter (reasonably) is, the better as long as it does not harm the creator. In addition, the State can determine the period of copyright protection through its regulations according to the country's ability.